Demands of the readers abroad for Soviet Lithuanian books as satisfied by book trade - Starkūnaitė-Jurkuvėnienė, Vanda; Kubickaitė, Valė (Knygotyra, 1983)
The article deals with the immediate source of the spreading of Soviet Lithuanian books abroad, the international book trade. The Export-Import Department of the Soviet Lithuanian Book Base cooperates with the all-Union Society “The International Book” which since 1930 has a monopoly of book trade with foreign countries. Meantime Lithuanian books are sold in more than sixty countries. Different problems of the Soviet Lithuanian book trade with foreign countries have been dealt with since 1955 in the articles by J. Bartkus, V. Mirkinas. S. Arnašius, M. Požarskas, B. Vaitkevičius, V. Aleknavičius etc. The customers are informed about Lithuanian publications meant for international book trade by special catalogues “Books in the Lithuanian Language from the USSR” In 1955–1976 readers abroad were recommended to buy over 400 books published by Soviet Lithuanian publishing houses; it made up almost 50% of all publications. In 1977 the criteria of book choice were changed; now the supply of publications has decreased almost by half. Lithuanian books are also advertised by the Union catalogue “Novyje knygi SSSR”. The book trade with foreign countries is influenced by the immediate contacts of our publishers with foreign publishers and representatives of book trade firms and organizations during the International Book Fairs and Exhibitions in Moscow. In 1955 when Soviet Lithuanian books started to be sold abroad the Republican Book Base had no direct contacts with foreign partners. From 1963 Lithuanian books have been sent directly to book firms abroad. In 1966 a special Export Group was set up which later was reorganized into the Export-Import Department. There is a great demand abroad for Lithuanian belles-lettres. The demand for Lithuanian books for children has also increased. Therefore special editions of books in Czech, Slovak. German and other languages are published. Readers abroad are also interested in books on history. Lithuanian fiction, linguistics. and books on art. More effectively demands abroad for Soviet Lithuanian books might be satisfied if more detailed investigations of the 25-year-old practice in book trade and the coordination and cooperation of the activities of the participating institutions and organizations were carried on.